2012
DOI: 10.1080/02331934.2011.587007
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic programming problems with generalized integrated chance constraints

Abstract: If the constraints in an optimization problem are dependent on a random parameter, we would like to ensure that they are fulfilled with a high level of reliability. The most natural way is to employ chance constraints. However, the resulting problem is very hard to solve. We propose an alternative formulation of stochastic programs using penalty functions. The expectations of penalties can be left as constraints leading to generalized integrated chance constraints, or incorporated into the objective as a penal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Finally, a comparison to mean-risk efficiency can be done similarly as in Kopa (2011). In future research, we will address sample approximation technique, see Branda (2012), to handle the tests with multivariate continuous distribution of asset returns.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a comparison to mean-risk efficiency can be done similarly as in Kopa (2011). In future research, we will address sample approximation technique, see Branda (2012), to handle the tests with multivariate continuous distribution of asset returns.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) . For other methodologies and solvers, we refer to Pflug and Pichler (2011) and Branda (2012) .…”
Section: Representing Hospital Capacitymentioning
confidence: 99%
“…It can be verified that under some conditions we obtain an optimal solution with desirable reliability by increasing the penalty parameter and solving the resulting problems. It can be even shown that under mild conditions the penalty approach and the chance constrained problem are asymptotically equivalent; see Branda [14,15], Branda and Dupačová [16], and Ermoliev et al [17]. Recently, the equivalence was stated under exact penalization where a finite penalty parameter is sufficient to obtain a local optimal solution which is permanently feasible with respect to the random constraints; see Branda [18].…”
Section: Advances In Decision Sciencesmentioning
confidence: 99%